Correction to: The recurrent missense mutation p.(Arg367Trp) in YARS1 causes a distinct neurodevelopmental phenotype (Journal of Molecular Medicine, (2021), 10.1007/s00109-021-02124-9) - Averdunk, Luisa; Sticht, Heinrich; Surowy, Harald; Luedecke, Hermann-Josef; Koch-Hogrebe, Margarete; Alsaif, Hessa S.; Kahrizi, Kimia; Alzaidan, Hamad; Alawam, Bashayer S.; Tohary, Mohamed; Kraus, Cornelia; Endele, Sabine; et al. (Journal of Molecular Medicine, 2021)
In the published original paper, Fig. 1 is incomplete. Only Fig. 1a is shown. This erratum corrects Fig. 1 and adds the missing panel 1 b-f to the article.
CRIS-Team Scopus Importer:2021-10-29

De novo missense mutations in the NAA10 gene cause severe non-syndromic developmental delay in males and females - Popp, Bernt; Stove, Svein I.; Endele, Sabine; Myklebust, Line M.; Hoyer, Juliane; Sticht, Heinrich; Azzarello-Burri, Silvia; Rauch, Anita; Arnesen, Thomas; Reis, André (European journal of human genetics, 2015)
Recent studies revealed the power of whole-exome sequencing to identify mutations in sporadic cases with non-syndromic intellectual disability. We now identified de novo missense variants in NAA10 in two unrelated individuals, a boy and a girl, with severe global developmental delay but without any major dysmorphism by trio whole-exome sequencing. Both de novo variants were predicted to be deleterious, and we excluded other variants in this gene. This X-linked gene encodes N-alpha-acetyltransferase 10, the catalytic subunit of the NatA complex involved in multiple cellular processes. A single hypomorphic missense variant p.(Ser37Pro) was previously associated with Ogden syndrome in eight affected males from two different families. This rare disorder is characterized by a highly recognizable phenotype, global developmental delay and results in death during infancy. In an attempt to explain the discrepant phenotype, we used in vitro N-terminal acetylation assays which suggested that the severity of the phenotype correlates with the remaining catalytic activity. The variant in the Ogden syndrome patients exhibited a lower activity than the one seen in the boy with intellectual disability, while the variant in the girl was the most severe exhibiting only residual activity in the acetylation assays used. We propose that N-terminal acetyltransferase deficiency is clinically heterogeneous with the overall catalytic activity determining the phenotypic severity.
EVALuna2:9247

Exome sequencing unravels unexpected differential diagnoses in individuals with the tentative diagnosis of Coffin-Siris and Nicolaides-Baraitser syndromes - Bramswig, Nuria C.; Luedecke, Hermann-Josef; Alanay, Yasemin; Albrecht, Beate; Barthelmie, Alexander; Boduroglu, Koray; Braunholz, Diana; Caliebe, Almuth; Chrzanowska, Krystyna H.; Czeschik, Johanna Christina; Endele, Sabine; Graf, Elisabeth; et al. (Human genetics, 2015)
Coffin-Siris syndrome (CSS) and Nicolaides-Baraitser syndrome (NCBRS) are rare intellectual disability/congenital malformation syndromes that represent distinct entities but show considerable clinical overlap. They are caused by mutations in genes encoding members of the BRG1- and BRM-associated factor (BAF) complex. However, there are a number of patients with the clinical diagnosis of CSS or NCBRS in whom the causative mutation has not been identified. In this study, we performed trio-based whole-exome sequencing (WES) in ten previously described but unsolved individuals with the tentative diagnosis of CSS or NCBRS and found causative mutations in nine out of ten individuals. Interestingly, our WES analysis disclosed overlapping differential diagnoses including Wiedemann-Steiner, Kabuki, and Adams-Oliver syndromes. In addition, most likely causative de novo mutations were identified in GRIN2A and SHANK3. Moreover, trio-based WES detected SMARCA2 and SMARCA4 deletions, which had not been annotated in a previous Haloplex target enrichment and next-generation sequencing of known CSS/NCBRS genes emphasizing the advantages of WES as a diagnostic tool. In summary, we discuss the phenotypic and diagnostic challenges in clinical genetics, establish important differential diagnoses, and emphasize the cardinal features and the broad clinical spectrum of BAF complex disorders and other disorders caused by mutations in epigenetic landscapers.
EVALuna2:9264

Loss-of-function variants in HIVEP2 are a cause of intellectual disability - Srivastava, Siddharth; Engels, Hartmut; Schanze, Ina; Cremer, Kirsten; Wieland, Thomas; Menzel, Moritz; Schubach, Max; Biskup, Saskia; Kreiss, Martina; Endele, Sabine; Strom, Tim M.; Wieczorek, Dagmar; et al. (European journal of human genetics, 2016)
Intellectual disability (ID) affects 2-3% of the population. In the past, many genetic causes of ID remained unidentified due to its vast heterogeneity. Recently, whole exome sequencing (WES) studies have shown that de novo variants underlie a significant portion of sporadic cases of ID. Applying WES to patients with ID or global developmental delay at different centers, we identified three individuals with distinct de novo variants in HIVEP2 (human immunodeficiency virus type I enhancer binding protein), which belongs to a family of zinc-finger-containing transcriptional proteins involved in growth and development. Two of the variants were nonsense changes, and one was a 1 bp deletion resulting in a premature stop codon that was reported previously without clinical detail. In silico prediction programs suggest loss-of-function in the mutated allele leading to haploinsufficiency as a putative mechanism in all three individuals. All three patients presented with moderate-to-severe ID, minimal structural brain anomalies, hypotonia, and mild dysmorphic features. Growth parameters were in the normal range except for borderline microcephaly at birth in one patient. Two of the patients exhibited behavioral anomalies including hyperactivity and aggression. Published functional data suggest a neurodevelopmental role for HIVEP2, and several of the genes regulated by HIVEP2 are implicated in brain development, for example, SSTR-2, c-Myc, and genes of the NF-?B pathway. In addition, HIVEP2-knockout mice exhibit several working memory deficits, increased anxiety, and hyperactivity. On the basis of the genotype-phenotype correlation and existing functional data, we propose HIVEP2 as a causative ID gene.
EVALuna2:9305

Loss-of-function variants of SETD5 cause intellectual disability and the core phenotype of microdeletion 3p25.3 syndrome - Kuechler, Alma; Zink, Alexander M.; Wieland, Thomas; Luedecke, Hermann-Josef; Cremer, Kirsten; Salviati, Leonardo; Magini, Pamela; Najafi, Kimia; Zweier, Christiane; Czeschik, Johanna Christina; Aretz, Stefan; Endele, Sabine; et al. (European journal of human genetics, 2015)
Intellectual disability (ID) has an estimated prevalence of 2-3%. Due to its extreme heterogeneity, the genetic basis of ID remains elusive in many cases. Recently, whole exome sequencing (WES) studies revealed that a large proportion of sporadic cases are caused by de novo gene variants. To identify further genes involved in ID, we performed WES in 250 patients with unexplained ID and their unaffected parents and included exomes of 51 previously sequenced child-parents trios in the analysis. Exome analysis revealed de novo intragenic variants in SET domain-containing 5 (SETD5) in two patients. One patient carried a nonsense variant, and the other an 81 bp deletion located across a splice-donor site. Chromosomal microarray diagnostics further identified four de novo non-recurrent microdeletions encompassing SETD5. CRISPR/Cas9 mutation modelling of the two intragenic variants demonstrated nonsense-mediated decay of the resulting transcripts, pointing to a loss-of-function (LoF) and haploinsufficiency as the common disease-causing mechanism of intragenic SETD5 sequence variants and SETD5-containing microdeletions. In silico domain prediction of SETD5, a predicted SET domain-containing histone methyltransferase (HMT), substantiated the presence of a SET domain and identified a novel putative PHD domain, strengthening a functional link to well-known histone-modifying ID genes. All six patients presented with ID and certain facial dysmorphisms, suggesting that SETD5 sequence variants contribute substantially to the microdeletion 3p25.3 phenotype. The present report of two SETD5 LoF variants in 301 patients demonstrates a prevalence of 0.7% and thus SETD5 variants as a relatively frequent cause of ID.
EVALuna2:9248

Mutations affecting the SAND domain of DEAF1 cause intellectual disability with severe speech impairment and behavioral problems - Vulto-Van Silfhout, Anneke T.; Rajamanickam, Shivakumar; Jensik, Philip J.; Vergult, Sarah; De Rocker, Nina; Newhall, Kathryn J.; Raghavan, Ramya; Reardon, Sara N.; Jarrett, Kelsey; Mcintyre, Tara; Bulinski, Joseph; Ownby, Stacy L.; et al. (American Journal of Human Genetics, 2014)
Recently, we identified in two individuals with intellectual disability (ID) different de novo mutations in DEAF1, which encodes a transcription factor with an important role in embryonic development. To ascertain whether these mutations in DEAF1 are causative for the ID phenotype, we performed targeted resequencing of DEAF1 in an additional cohort of over 2,300 individuals with unexplained ID and identified two additional individuals with de novo mutations in this gene. All four individuals had severe ID with severely affected speech development, and three showed severe behavioral problems. DEAF1 is highly expressed in the CNS, especially during early embryonic development. All four mutations were missense mutations affecting the SAND domain of DEAF1. Altered DEAF1 harboring any of the four amino acid changes showed impaired transcriptional regulation of the DEAF1 promoter. Moreover, behavioral studies in mice with a conditional knockout of Deaf1 in the brain showed memory deficits and increased anxiety-like behavior. Our results demonstrate that mutations in DEAF1 cause ID and behavioral problems, most likely as a result of impaired transcriptional regulation by DEAF1.
EVALuna2:9219

Mutations in the BAF-Complex Subunit DPF2 Are Associated with Coffin-Siris Syndrome - Vasileiou, Georgia; Vergarajauregui, Silvia; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, Marion; Bramswig, Nuria C.; Albrecht, Beate; Clayton-Smith, Jill; Morton, Jenny; Tomkins, Susan; et al. (American Journal of Human Genetics, 2018)
Variants affecting the function of different subunits of the BAF chromatin-remodelling complex lead to various neurodevelopmental syndromes, including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental-delay disorders. Here, we report eight heterozygous de novo variants (one frameshift, two splice site, and five missense) in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome, including coarse facial features, global developmental delay, intellectual disability, speech impairment, and hypoplasia of fingernails and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Pull-down assays of recombinant proteins and histone peptides revealed that a subset of the identified missense variants abolish or impaire DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD finger structural integrity and cohesion and most likely an aberrant recognition of histone modifications. Furthermore, the overexpression of these variants in HEK293 and COS7 cell lines was associated with the formation of nuclear aggregates and the recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in the affected individuals indicated that the aberrant transcripts escape nonsense-mediated decay. Altogether, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant-negative mechanism of pathogenicity.

Mutations in the BAF-complex subunit DPF2 are associated with Coffin-Siris syndrome - Vasileiou, G.; Vergarajauregui, S.; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, M.; Bramswig, N. C.; Albrecht, B.; Clayton-Smith, J.; Morton, J.; Tomkins, S.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

The recurrent missense mutation p.(Arg367Trp) in YARS1 causes a distinct neurodevelopmental phenotype - Averdunk, Luisa; Sticht, Heinrich; Surowy, Harald; Luedecke, Hermann-Josef; Koch-Hogrebe, Margarete; Alsaif, Hessa S.; Kahrizi, Kimia; Alzaidan, Hamad; Alawam, Bashayer S.; Tohary, Mohamed; Kraus, Cornelia; Endele, Sabine; et al. (Journal of Molecular Medicine, 2021)
Pathogenic variants in aminoacyl-tRNA synthetases (ARS1) cause a diverse spectrum of autosomal recessive disorders. Tyrosyl tRNA synthetase (TyrRS) is encoded by YARS1 (cytosolic, OMIM*603,623) and is responsible of coupling tyrosine to its specific tRNA. Next to the enzymatic domain, TyrRS has two additional functional domains (N-Terminal TyrRS(Mini) and C-terminal EMAP-II-like domain) which confer cytokine-like functions. Mutations in YARS1 have been associated with autosomal-dominant Charcot-Marie-Tooth (CMT) neuropathy type C and a heterogenous group of autosomal recessive, multisystem diseases. We identified 12 individuals from 6 families with the recurrent homozygous missense variant c.1099C > T;p.(Arg367Trp) (NM_003680.3) in YARS1. This variant causes a multisystem disorder with developmental delay, microcephaly, failure to thrive, short stature, muscular hypotonia, ataxia, brain anomalies, microcytic anemia, hepatomegaly, and hypothyroidism. In silico analyses show that the p.(Arg367Trp) does not affect the catalytic domain responsible of enzymatic coupling, but destabilizes the cytokine-like C-terminal domain. The phenotype associated with p.(Arg367Trp) is distinct from the other biallelic pathogenic variants that reside in different functional domains of TyrRS which all show some common, but also divergent clinical signs [(e.g., p.(Phe269Ser)-retinal anomalies, p.(Pro213Leu)/p.(Gly525Arg)-mild ID, p.(Pro167Thr)-high fatality)]. The diverse clinical spectrum of ARS1-associated disorders is related to mutations affecting the various non-canonical domains of ARS1, and impaired protein translation is likely not the exclusive disease-causing mechanism of YARS1- and ARS1-associated neurodevelopmental disorders. Key messages The missense variant p.(Arg367Trp) in YARS1 causes a distinct multisystem disorder. p.(Arg367Trp) affects a non-canonical domain with cytokine-like functions. Phenotypic heterogeneity associates with the different affected YARS1 domains. Impaired protein translation is likely not the exclusive mechanism of ARS1-associated disorders.
CRIS-Team WoS Importer:2021-10-01